Understanding the Impact of Green Human Resource Management Practices and Dynamic Sustainable Capabilities on Corporate Sustainable Performance: Evidence From the Manufacturing Sector - Khaskhely, Mahvish Kanwal; Qazi, Sarah Wali; Khan, Naveed R.; Hashmi, Tooba; Chang, Asma Abdul Rahim (Frontiers in Psychology, 2022)
Pakistan ranks as the eighth most vulnerable country on the 2021 global climate change vulnerability index. Partially, this perilous position is attributed to unsustainable practices in the large-scale manufacturing sector since its contribution to carbon emission is among the highest in the economy. These serious environmental challenges impede the attainment of sustainable development goals that concern responsible consumption and production. In manufacturing organizations, there are an ongoing debate regarding sustainable human resource management (HRM) determinants, which can promote sustainable performance. In this regard, green human resource management (GHRM) practices and dynamic sustainable capabilities are significant components as they have a unique role in transforming corporations into sustainable organizations. However, there is a dearth of evidence regarding the impact of individual GHRM practices, such as green recruitment and selection, green pay and reward, and sustainable capabilities like monitoring and re-configuration, in improving the corporate environmental and social performance. Hence, an empirical investigation regarding the association among these macro-level components with the corporate environmental and social performance through partial least squares structural equation modeling (PLS-SEM) is conducted. The findings inferred from 396 employees affiliated with six large-scale industries substantiate the main hypotheses of this study. It is empirically confirmed that GHRM and dynamic sustainable capabilities significantly and positively impact corporate sustainable performance. This research contributes to the literature by employing dynamic capabilities approach and a dynamic resource-based view (RBV) to explicate how corporations can benefit from the interplay of sustainable capabilities and GHRM functions. Hence, in the absence of a significant predictive model, this research is the first of its kind to isolate macro-level antecedents of sustainable HRM to find their impact on corporate sustainable performance in a developing country context. The study recommends that the management should prioritize the acquisition of monitoring capabilities and hiring environmentally conscious employees to achieve social equity and ecological conservation goals.